Integrated Micro-Endodontic Surgical Management of a Persistent Periapical Lesion in a Maxillary Central Incisor: A Case Report - tanty frima; Denny Nurdin; Opik Taofik Hidayat (Maranatha Christian University, 2026)
Abstract: Background:Managing persistent periapical lesions in anterior teeth of adolescent patient presents a clinical challenge. While conventional root canal therapy remains the first line of treatment, certain cases may not respond adequately, especially when the lesion involves extensive bone destruction. In such scenarios, a surgical endodontic intervention becomes a vital alternative to preserve the affected tooth. Case Report: A 15-year-old female patient presented with tooth 11 previously treated endodontically. However, the CBCT revealed a periapical radiolucency associated with possible apical root crack and cortical bone perforation. Given the lesion’s extent and the limited prognosis of nonsurgical retreatment, a decision was made to perform a micro-endodontic surgical procedure. The procedure involved a submarginal Ochsenbein–Luebke flap, apical resection, curettage, root-end preparation, and retrograde obturation with mineral trioxide aggregate (MTA). To enhance healing, bone grafting and membrane placement were performed prior to wound closure. Histopathological analysis of the excised lesion confirmed a periapical cyst. Objective: This case underscores the critical role of accurate diagnosis using advanced imaging such as CBCT and highlights the value of a multidisciplinary approach in treating persistent lesions. The use of biocompatible regenerative materials like MTA and bone grafts can promote healing and maintains anterior aesthetics in adolescent patients. Conclusion: Micro-endodontic surgical management offers a predictable and conservative solution, especially for persistent periapical lesion in previously treated teeth, ensuring both functional preservation and aesthetic integrity. Keywords: Apicoectomy, Bone graft, Cone-Beam Computed Tomography, Maxillary central incisor, Periapical cyst, MTA, Microsurgery.